The Influence of Doll Therapy in Iranian Elderly: A Randomized Trial Study - Mirzakhani Araghi, Navid; Dabiri Golchin, Minoo; Golshan Tafti, Mohammad; Dabiri Golchin, Mahsa; Fallah, Samaneh; Yazdani, Farzaneh (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Many elderly populations feel lonely and it has a significant negative relationship to their health status. Doll therapy may seem childish and ridiculous for adults, but it can have an undeniable effect on the elderly’s health. The positive impact of doll therapy has already been proven in depression and dementia. The aim of this study was to evaluate the influence of doll therapy in agitation, aggression, and interactions of elderly people.. Methods and Materials: Sixty elderly people were selected at the Kahrizak charity foundation in Tehran. Ten different dolls (5 popular characters and 5 newborn dolls in neutral and specific genders) were presented to them. Their reaction to all dolls recorded (no reaction: 0, watch closely: 1, caring the doll: 2, communicating with the doll: 3) and each elderly chose one doll to keep it for 6 weeks. The aggression, agitation, and interactions with other elderly people and also with the nursing home staff were asked before and after a 6-week period of doll therapy from their caregivers by the Likert scale. Results: Twelve of 60 samples exited from the study because they were unwilling. Twenty elderly did not meet the inclusion criteria. After 6 weeks, 8 subjects donated their dolls to someone else. Eventually 26, people stayed in the study, and their dada were analyzed. The highest doll selection rate was for neutral gender dolls and popular dolls were almost ignored by the elderly. Paired sample T-test showed significant differences for aggression and agitation (P<0.001) and also interactions (P<0.05) Conclusion: Although the sample size after all exclusion seems to be small, we can conclude that doll therapy is not a consistent method for all elderly, but it is beneficial and can improve their relationships and reduce their aggression and agitation. More researches with larger samples are suggested. Keywords: Doll therapy, Elderly, Play therapy